Anemic psittacine birds in Rio de Janeiro: A focus on erythrogram analysis (Research, Society and Development, 2025)
Psittacines have become increasingly popular as pets in Brazil, generating a growing demand for specialized veterinarians in the country. The blood count is an essential complementary test for screening and monitoring the general health of these animals. The aim of this study was to identify the altered hematological parameters in erythrograms of birds of the Psittaciformes order, with a focus on individuals that showed values below the reference limits. The database analyzed 362 hemograms taken between January 2022 and May 2025 at a veterinary clinical pathology laboratory located in the state of Rio de Janeiro. Of these, 80 birds were identified as anemic. The statistical analysis considered factors such as age group, gender and morphological classification of anemia. The overall prevalence of anemia was 22%, varying between the species Agapornis sp. (29%), Amazona aestiva (19%), Nymphicus hollandicus (19%) and Psittacula krameri (34%), with the majority of cases classified as normocytic normochromic anemia. Notably, Amazona aestiva showed the greatest morphological diversity. A higher prevalence of anemia was observed in adult males, except in Nymphicus hollandicus, where females predominated. This epidemiological study raises the hypothesis that more rigorous standardization of erythrogram normality intervals could improve the understanding and interpretation of anaemic processes in psittacine birds. It is hoped that the results obtained will encourage further research, strengthening psittacine hematology, especially in a scenario where these birds are on the rise in Brazilian homes.